Business case 3M Chile, Brooms & Mops (A) Opportunity - Oliva, Ismael (Estudios de Administración, 2012)
In June 2005, 3M's parent company established the challenge of doubling the size of the business in a three-year period. In this way, the work horizon for the next few years was established in a large global technology corporation, with sales of over USD 20 billion and with leadership positions in the electronics, telecommunications, industry, consumer products and office, care health, safety, among others. At 3M Chile, the Country Manager of the Consumer and Office Division, Guillermo Ochoa, envisioned that for his business lines, he would not be able to meet the challenge of doubling his sales volume if he maintained the way he had performed until then. Inspired by the philosophy of the global CEO, he discovered that there were new lines of complementary products, that they were not part of the current core of the business, that for the same reason there were no factories available within the company and they were not marketed. In January 2006, Ochoa had to make the decision whether or not to develop these products for the Chilean market based on the business opportunity that he was leading and the challenge that had been imposed on him. From 2001 to 2005 W. James McNearny Jr. was the Chairman of the Board and CEO of 3M. He marked important changes in the way the company faced market challenges. With his 19 years of experience at General Electric, McNearny introduced the Six Sigma philosophy to 3M; not only as a work methodology, but rather as the possibility of turning it upside down. He argued that Six Sigma should be embedded within the DNA of the company and its workers. That through the development of the DMAIC1 process improvement, plus the implementation of the new product introduction methodology, the implicit risk would be reduced and the chances of hitting new businesses would be considerably increased. To the above, a concept developed by its founders was added: Own your Destiny (be the owner of your own destiny), which challenged the organization to break down the barriers to creativity, and to look at the future in a different way, to grow in markets even more competitive than today.